Large-scale identification of membrane proteins with properties favorable for crystallization - Kim, Jared (Protein Sci, 2015)
Membrane protein crystallography is notoriously difficult due to challenges in protein expression and issues of degradation and structural stability. We have developed a novel method for large-scale screening of native sources for integral membrane proteins that have intrinsic biochemical properties favorable for crystallization. Highly expressed membrane proteins that are thermally stable and nonaggregating in detergent solutions were identified by mass spectrometry from Escherichia coli, Saccharomyces cerevisiae, and Sus scrofa cerebrum. Many of the membrane proteins identified had been crystallized previously, supporting the promise of the approach. Most identified proteins have known functions and include high-value targets such as transporters and ATPases. To validate the method, we recombinantly expressed and purified the yeast protein, Yop1, which is responsible for endoplasmic reticulum curvature. We demonstrate that Yop1 can be purified with the detergent dodecylmaltoside without aggregating.